2017
DOI: 10.1071/sh16198
|View full text |Cite
|
Sign up to set email alerts
|

How partnership type and HIV seroconcordance affect HIV transmission risk in regular sexual partnerships: a cross-sectional survey of Australian gay and bisexual men

Abstract: Abstract. Background: Regular sexual partnerships among gay and bisexual men (GBM) who practice condomless anal intercourse (CLAI) have not been well characterised in terms of partnership type, HIV seroconcordance and risk of HIV transmission. Primarily sexual regular partnerships, although commonly reported by gay men, have largely been ignored in research and HIV prevention. Among regular partners reporting CLAI with each other, we determined factors differentiating romantic or committed relationships from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…We found no evidence that men with HIV-negative primary partners had a specific PrEP dosing preference, nor evidence of an association between PrEP preference and engaging in receptive CLAI with other regular or casual partners of HIV-positive or unknown status. While these partner types can pose a much higher risk of HIV transmission than an HIV-positive primary partner ( 35 , 36 ), they may not be associated with the same prolonged anxiety or association with HIV. Thus, other HIV prevention strategies can be negotiated with other regular and casual partners, as compared with HIV-positive main regular partners.…”
Section: Discussionmentioning
confidence: 99%
“…We found no evidence that men with HIV-negative primary partners had a specific PrEP dosing preference, nor evidence of an association between PrEP preference and engaging in receptive CLAI with other regular or casual partners of HIV-positive or unknown status. While these partner types can pose a much higher risk of HIV transmission than an HIV-positive primary partner ( 35 , 36 ), they may not be associated with the same prolonged anxiety or association with HIV. Thus, other HIV prevention strategies can be negotiated with other regular and casual partners, as compared with HIV-positive main regular partners.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 While the majority of research continues to focus on differences between individuals to explain sexual risk taking, 10 a growing body of research suggests that a significant proportion of the variability in condom use during anal intercourse exists within individuals across different sexual partnerships. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Within the sexual partnerships of MSM, the strongest associations between condom use and partnership characteristics have been observed based on partnership type and agreement of serostatus between partners (seroconcordance). Mathematical models based on data from five US cities during the 2003-2005 cycle of the National HIV Behavioral Surveillance (NHBS) System suggested that 68% of HIV transmissions among MSM occurred within main partnerships, as a result of the higher number of sex acts and lower condom use during anal sex with main partners compared to casual or exchange partners (i.e., those where money and/or other gifts were exchanged for sex).…”
Section: Introductionmentioning
confidence: 99%
“…High-profile research evidence regarding TasP and PrEP was released throughout the course of the study, and consequently, individual and community notions of what constituted "safe(r) sex" among gay men were dynamic. Thus, CLAI was common, with three-quarters of couples engaging in at least some CLAI during follow-up, higher than estimates reported in previous studies of male serodiscordant couples [7,26,27,30,31]. Nearly half of anal intercourse Perceived detectable viral load, actually <200 copies ("not correct") 287 (16.1) 50 (4.9) 34 (7.9) c 203 (60.8) b…”
Section: Discussionmentioning
confidence: 83%
“…a Denotes significant differences between countries at the p < 0.001 level using univariable logistic regression, with Australia as the referent category; b denotes significant differences between countries at the p < 0.01 level using univariable logistic regression, with Australia as the referent category. other studies of serodiscordant couples [43], but this measure may no longer be sufficient to identify "high risk" [31,44]. Finally, previous analysis determined that risk is highest in the first year of a gay male serodiscordant relationship [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation